MODEL PEMBELAJARAN BERBASIS PROYEK SEBAGAI STRATEGI PEMBELAJARAN BERPUSAT PADA SISWA SEKOLAH DASAR - Purwantini, Rina; Yuliastuti, Erlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the Project Based Learning (PjBL) Model as a student-centered learning strategy in elementary schools through a literature study approach. This study uses a qualitative method with data collection techniques in the form of literature reviews from books, national and international journal articles, and relevant academic documents. Data were analyzed using content analysis techniques to identify concepts, characteristics, implementation steps, advantages, and challenges of implementing PjBL in the context of 21st-century education. The results of the study indicate that PjBL is based on constructivism theory and the principle of learning by doing that positions students as active subjects in constructing knowledge through real experiences and collaborative work. This model has been proven to be able to increase learning motivation, student engagement, critical thinking skills, creativity, communication, and collaboration. In addition, PjBL also encourages student independence and responsibility in managing the learning process. However, its implementation requires careful planning, teacher readiness, and adequate support from facilities and infrastructure. Overall, PjBL is relevant to be implemented as an innovative learning strategy to support adaptive educational transformation and oriented towards the development of 21st-century competencies.